Synergistic stabilization of expansive soil using ultrafine high-reactivity fly ash and calcium carbide slag: performance optimization and microstructural insights - Qiu, Xingwang; Lai, Zhenrui; Zuo, Jinyu; Li, Wenwei (Frontiers in Materials, 2025)
Expansive soils pose significant geotechnical challenges to infrastructure due to their moisture-induced shrink-swell behavior. Traditional stabilizers often have environmental or cost drawbacks. This study investigates a sustainable stabilization technique using a synergistic binder system composed of ultrafine high-reactivity fly ash (UHFA) and calcium carbide slag (CCS), two industrial by-products. The primary contribution of this research is the systematic optimization of both the binder ratio and total dosage to maximize engineering performance. A comprehensive laboratory program, including compaction, free swelling rate, and unconfined compressive strength (UCS) tests, was conducted, supplemented by scanning electron microscopy (SEM) and X-ray Diffraction (XRD) for microstructural analysis. Results indicate that an optimal UHFA:CCS mass ratio of 7:3 and a total binder content of 15% yields the best performance. Under these optimal conditions, the 28-day free swelling rate was reduced to 27.4%, effectively reclassifying the soil as non-expansive, while the UCS reached a peak of 378.1 kPa, approximately 4.5 times that of the untreated soil. Mechanistically, SEM and XRD analyses revealed that CCS provides an alkaline environment that activates the pozzolanic reactivity of UHFA, generating extensive C-S-H and C-A-H gels. These gels fill pores and bind soil particles into a dense, stable skeleton, while Ca2+ ion exchange further mitigates swelling potential. This study demonstrates that the optimized UHFA-CCS system is a high-performance, resource-efficient technology for mitigating expansive soil issues.